In-Vitro Phenotypic Response of Human Osteoblasts to Different Degrees of Titanium Surface Roughness - Muataz A. Osman; Rasha A. Alamoush; Evgeny Kushnerev; Kevin G. Seymour; Susan Shawcross; Julian M. Yates (MDPI AG, 2022)
Objectives: This study aimed to investigate human osteoblast (HOB) responses towards different degrees of titanium (Ti) implant surface roughness. Methods: Four degrees of Ti surface roughness were investigated on a micrometer roughness scale: smooth (S: 0.08-0.1 µm), minimally rough (MM: 0.3-0.5 µm), moderately rough (MR: 1.2-1.4 µm), and rough (R: 3.3-3.7 µm). HOB cells were cultured, expanded, and maintained according to the supplier's protocol. Cell proliferation and cytotoxicity were assessed at day 1, 3, 5, and 10 using alamarBlue and lactate dehydrogenase colorimetric assays. Data were analyzed with one-way ANOVA, two-way ANOVA, and Tukey's post hoc test (p = 0.05 for all tests). Results: There was no significant difference in the cell proliferation or cytotoxicity of the HOB cells in contact with the different degrees of Ti surface roughness. There was, however, a significant time effect on cell proliferation (p < 0.0001) with different exposure durations for each roughness degree. Furthermore, a positive correlation (non-significant) between proliferation and cytotoxicity was observed for all investigated degrees of surface roughness. Conclusion: All investigated roughness degrees showed comparable HOB proliferation, with the MR surface presenting the highest percentage, followed by the R, MM, ad S, surfaces, respectively. The S surface showed the highest cytotoxic effect on HOBs; however, it did not reach the cytotoxic level suggested by the ISO for any medical device to be considered cytotoxic.